THE MOZAIC EFFECT ON THE IMPROVEMENT OF FINE MOTOR SKILLS OF 3-4 YEARS OLD CHILDREN IN INTEGRATED HEALTH CARE CENTER, THE WORKING AREA OF PUBLIC HEALTH CENTER WAENA JAYAPURA CITY. - Suryati Romauli (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
The Child development speed is unique; it varies due to the child’s nature and its stimulants. Lack of stimulants will affect late fine motoric development of children. Data from the Waena Health Center inform, 190 toddlers have impaired fine motor development. This research objective was to determine the effect of mosaic techniques on the enhancement of fine motor skills in children aged 3-4 years in Integrated Health Care Waena area, Jayapura City. A quantitative descriptive research was done with Two Group Pretest-Postest Group Design. The results before the mosaic technique showed in intervention group, had dubious fine motor skills (55.6%) and 16.6% deviant. Whereas in the control group had dubious fine motor skills (83.3%) and 5.6% deviant. After using mosaic technique the intervention group had fine motor skills (77.8%) and small part doubted (22.2%). The average score after improving fine motor skills in the intervention group was 8, while the control group was 7.1 with independent t-test statistical test at a significance value of 95% ( = 0.05) obtained p-value 0.042 or p <α (0.05), thus there is an effect of mosaic techniques on improving fine motor skills of children at the Integrated Health Care Waena area, Jayapura City. Keyword: Mozaik Technique, Fine motor skill, children age 3-4 tahun